2017
DOI: 10.1016/j.landusepol.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Does the crop diversification measure impact EU farmers’ decisions? An assessment using an Individual Farm Model for CAP Analysis (IFM-CAP)

Abstract: This paper presents the first EU-wide individual farm level model (IFM-CAP-Individual Farm Model for CAP Analysis) to assess the impacts of the crop diversification measure introduced by the 2013 CAP reform as part of CAP 'greening'. Based on Positive Mathematical Programming, IFM-CAP simulates the behaviour of each individual farmer in the EU-FADN (Farm Accountancy Data Network) database, under the policy constraint of crop diversification and provides distributional impacts over the entire EU farm population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 38 publications
(51 reference statements)
1
37
0
1
Order By: Relevance
“…Other approaches and theoretical frameworks, in agronomy or economics, could have been used to analyze the increase in areas of major crops and the decline of minor crops, and to model these trends. Several studies, based on such disciplinary approaches, are quoted in our paper (for example, in agronomy, Schott et al 2010;Ponisio et al 2015;Zimmer et al 2016;in economics, Fares 2006;Filippi et al 2008;Louhichi et al 2017). However, the complex and systemic characters of specialization led us to overpass these disciplinary approaches, to adopt a holistic perspective of the involved socio-technical factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other approaches and theoretical frameworks, in agronomy or economics, could have been used to analyze the increase in areas of major crops and the decline of minor crops, and to model these trends. Several studies, based on such disciplinary approaches, are quoted in our paper (for example, in agronomy, Schott et al 2010;Ponisio et al 2015;Zimmer et al 2016;in economics, Fares 2006;Filippi et al 2008;Louhichi et al 2017). However, the complex and systemic characters of specialization led us to overpass these disciplinary approaches, to adopt a holistic perspective of the involved socio-technical factors.…”
Section: Resultsmentioning
confidence: 99%
“…Due to these strong links between impediments, the lock-in is systemic: any path towards diversification will necessarily rely on the simultaneous and organized mobilization of many actors (Geels 2002). It seems clear that a public policy, which would only contain measures intended for farmers, cannot be sufficient to enhance diversification (Louhichi et al 2017). The proof was given in France in 2010-2011, when public authorities aimed to increase land areas in pulses, by proposing a specific incentive to farmers.…”
Section: Interconnected Self-reinforcement Mechanismsmentioning
confidence: 99%
“…Their results show that the environmental impacts of greening are small, although greater effects can be pointed out in the regions with a larger percentage of intensive farms [17]. Louhichi et al (2017), using an EU-wide individual farm level model, show that the effects of the crop diversification practice on the EU farming sector are rather small. At the aggregate EU level, the proportion of the area that was reallocated due to the diversification measure represents less than 1% of the total agricultural area, and the crop production and income declines by less than 0.5%.…”
Section: Literature Review On Greeningmentioning
confidence: 99%
“…At the aggregate EU level, the proportion of the area that was reallocated due to the diversification measure represents less than 1% of the total agricultural area, and the crop production and income declines by less than 0.5%. At the individual farm level, the impacts could be more pronounced, although the number of farms affected by the measure remains small [18]. Finally, Hart et al (2017) evaluated the observed data regarding the payment for agricultural practices beneficial for the climate and the environment at European level.…”
Section: Literature Review On Greeningmentioning
confidence: 99%
“…The Common European Agricultural Policies are promoting crop diversification, by, for example, "greening" farms with over 10 ha of arable lands and regulating both the minimum number of crops and the surface of the main crops in the Usable Agricultural Area of the farm [5]. However, in a recent paper, Louhichi et al [6] concluded that the impact of this policy both on land use reallocation and on farm income of this policy remained rather small at the EU level. In France, Meynard et al [7] showed that the obstacles for crop diversification in 12 minor crops are linked to the difficult coordination between demand and supply, to the lack of technical references, and to the slower genetic progress compared to major crops.…”
Section: Introductionmentioning
confidence: 99%